MERGING ART AND INSTALLATION: EXHIBITION INSTALLATION IN THE 20th CENTURY - Georgiana BUȚ (Studia Universitatis Babeș-Bolyai. Philosophia)
This paper discusses exhibition installation as an aesthetic medium. Drawing on Germano Celant’s writing on installation, we advance an interpretation of artists’ engagement with installation resulting in room-size works in the first half of the 20th century, as part of the evolution of exhibition installation towards the convergence of art and design. The paper also address the problem of intermediality as discussed by Juliane Rebentisch, and its implications for installation and attempts to tests Rosalind Krauss’s reconception of the medium against Rebentisch’s criticism, while analyzing Krauss’s disapproval of installation art, including the room-size works of the avant-garde.